Cervix Cancer Spatial Modelling for Brachytherapy Applicator Analysis (Informatica, 2015)
Standard applicators for cervix cancer brachytherapy (BT) do not always enable a sufficient radiation dose coverage of the target structure (HR-CTV). The aim of this study was to develop methodology for building models of the BT target from a cohort of cervix cancer patients, which would enable BT applicator testing. In this paper we propose two model types, a spatial distribution model and a principal component model. Each of them can be built from data of several patients that includes medical images of arbitrary resolution and modality supplemented with delineations of HR-CTV structure, reconstructed applicator structure and eventual organs at risk (OAR) structures. The spatial distribution model is a static model providing probability distribution of the target in the applicator coordinate system, and as such provides information of the target region that applicators must be able to cover. The principal component model provides information of the target spatial variability described by only a few parameters. It can be used to predict specific extreme situations in the scope of sufficient applicator radiation dose coverage in the target structure as well as radiation dose avoidance in OARs. The results are generated 3D images that can be imported into existent BT planning systems for further BT applicator analysis and eventual improvements.